Prevalensi Kenyamanan dan Kemandirian di Kamar Mandi pada Lansia di Panti Sosial Tresna Wredha Wana Seraya Denpasar - Ida Bagus Gede Danny Ananta; I Putu Adiartha Griadhi (Universitas Udayana, 2017)
Being old is the natural process, with being old many degenerative disease springing with so human progressively will loseendurance against infection and many distortions of metabolic and structural. Injury in the bathroom can result in death , a problemthe bathroom is still very require improvement and the adjustment of a means. Ergonomic problems that they encountered isa mismatch between the size of a means of the bathroom with ability of body for the elderly. The overall health in the bodyfor the elderly can be measured by the body neurologis system change, muskuloskeletal system change. This research aboutcomfortable and independence of elderly patient at social workhouses on tresna wredha wana seraya in denpasar. Respondentsto this research were elderly patients older than 50 years and totally 31 person. Analysis technique used a descriptive crosssectional analysis. Sampling technique using questionnaires and interviews. Results of the research found that elderly patientsat social workhouses on tresna wredha wana seraya in denpasar as a whole have the independence and comfortable of thebathroom in the workhouses. Advice to Governments that administer workhouses was provide a bathroom to suit ergonomicscience in order to facilitate the elderly in everyday activities inside the bathroom. This will have an impact on elderly ergonomicpatients on long term.